THE PRAGMATIC ROLE OF PAREMIAS IN EXPRESSING SOCIAL NORMS IN UZBEK AND ENGLISH DISCOURSES - Qodirova , Ziyodaxon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
Paremias, as culturally embedded linguistic units, play a significant pragmatic role in expressing and regulating social norms within discourse. This study investigates how paremias function as pragmatic tools for articulating socially accepted values and behavioral expectations in Uzbek and English discourses. Adopting a discourse-pragmatic and contrastive approach, the research examines the illocutionary force, evaluative orientation, and contextual dependency of paremias as they are employed to convey normative meanings. The analysis reveals that in both Uzbek and English discourses, paremias are frequently used as indirect speech acts to legitimize social norms, mitigate face-threatening acts, and guide interpersonal behavior. However, notable cross-cultural differences emerge in the pragmatic realization of these functions. Uzbek paremias predominantly emphasize collectivist values, respect for social hierarchy, and moral responsibility, while English paremias tend to foreground individual autonomy, practical wisdom, and self-regulation. The findings demonstrate that paremias serve not merely as rhetorical devices but as dynamic pragmatic mechanisms through which social norms are enacted, reinforced, and negotiated in discourse.